2015
DOI: 10.1111/1750-3841.13144
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of Cinnamaldehyde, Citral, and Eugenol on Aflatoxin Biosynthetic Gene Expression and Aflatoxin B1 Biosynthesis in Aspergillus flavus

Abstract: In order to reveal the inhibitory effects of cinnamaldehyde, citral, and eugenol on aflatoxin biosynthesis, the expression levels of 5 key aflatoxin biosynthetic genes were evaluated by real-time PCR. Aspergillus flavus growth and AFB1 production were completely inhibited by 0.80 mmol/L of cinnamaldehyde and 2.80 mmol/L of citral. However, at lower concentration, cinnamaldehyde (0.40 mmol/L), eugenol (0.80 mmol/L), and citral (0.56 mmol/L) significantly reduced AFB1 production with inhibition rate of 68.9%, 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 40 publications
7
73
1
Order By: Relevance
“…constitute a significant portion of the microbial population in Daqu (19,21,22); their endospores survive under low-moisture conditions and at high temperatures (35). This study demonstrated that the count of spores increased during fermentation; the taxonomic identification of spore-forming bacteria matched prior reports on Daqu microbiota (Tables 1 and 2) (22,36). More surprisingly, 50% of the isolates of sporeformers were spoVA 2mob positive.…”
Section: Discussionsupporting
confidence: 83%
“…constitute a significant portion of the microbial population in Daqu (19,21,22); their endospores survive under low-moisture conditions and at high temperatures (35). This study demonstrated that the count of spores increased during fermentation; the taxonomic identification of spore-forming bacteria matched prior reports on Daqu microbiota (Tables 1 and 2) (22,36). More surprisingly, 50% of the isolates of sporeformers were spoVA 2mob positive.…”
Section: Discussionsupporting
confidence: 83%
“…Eugenol (0.80 mM) expresses no effect on the growth of Aspergillus flavus , but completely inhibits the aflatoxin B1 (AF B1) biosynthesis production with a inhibition rate of 95.4%, and this function is associated with downregulating the transcription level of aflatoxin biosynthetic genes as aflR, aflT, aflD, aflM, and aflP, and among these genes, aflP is highly downregulated about 2061‐folds (Liang et al., ). In a molecular system composed of 60 genes including 27 aflatoxin B biosynthetic genes and 33 regulatory factors, the expression of almost all genes of this AFB₁ biosynthesis cluster are significantly inhibited by eugenol (0.5 mM), and this transcriptomic effect is associated with downregulating two internal regulatory factors AflR and AflS, and is also influenced by the overexpression of two genes veA and mtfA, which are directly linked to AFB₁ cluster regulation (Caceres et al., ).…”
Section: The Antifungal Effect and Mechanism Of Clove Oil And Eugenolmentioning
confidence: 99%
“…In the last years, aflatoxin biosynthesis has been closely linked to fungal oxidative stress status (Montibus et al, 2013;Roze et al, 2013;Amare and Keller, 2014). Indeed, studies in Aspergilli demonstrated several molecules with antioxidant capacities are able to inhibit aflatoxin production (Jahanshiri et al, 2012;Liang et al, 2015). Furthermore, it has been demonstrated that a regulatory network of genes coding for stress response transcription factors (AtfB, SrrA, Ap-1 and MsnA)…”
Section: Introductionmentioning
confidence: 99%